A globális felmelegedésről (About the Global Warming) - Katalin M. Barna; Tamás Molnár (DETUROPE)
In recent years we can more and more often hear and read about the climate change and global warming. However, the global warming has already occured many times in Earth’s history – think of the alternation of ice ages and warmer periods – but the pace of the global warming which can cause for concern. British and American researchers say that even the carbon dioxide emissions quotas can not slow down the process moreover to full stopping of emissions could not to reverse the global warming. What will actually happen, we don’t know yet exactly, scientists are trying to set up different scenarios with the help of climate modeling. As the 5th of IPCC report says, people are responsible for the climate change at least 95 percent. Due to the fact the climate change has become a global phenomenon so the need for intervention is not an issue anymore thus only the extensive international cooperation can correct reply for global challanges. Beside the environmental and physiological effects, there are economic effects of climate change which costs may be 5-20% of GDP if we don’t intervene in processes while prevention costs of the most serious consequences are not expected to reach 1% of GDP. However, do not forget that the social and enterprise-level acceptance is the foundation of every step which counterbalance the global warming process. A part of the society is still sceptical about the impacts of climate change, in this case the development of appropriate communication is the solution. Among the companies the acceptance is wider as today the use of an environmentally friendly technology is a competitive advantage so these technologies have become a main factor of the long-term survival.